Suppression of the growth and metastasis of mouse melanoma by Taenia crassiceps and Mesocestoides corti tapeworms - Schreiber, Manfred; Macháček, Tomáš; Vajs, Vojtěch; Šmídová, Barbora; Majer, Martin; Hrdý, Jiří; Tolde, Ondřej; Brábek, Jan; Rösel, Daniel; Horák, Petr (Frontiers in Immunology, 2024)
Cancer is still one of the leading causes of death, with an estimated 19.3 million new cases every year. Our paper presents the tumor-suppressing effect of Taenia crassiceps and Mesocestoides corti on B16F10 melanoma, the intraperitoneal application of which followed the experimental infection with these tapeworms, resulting in varying degrees of effectiveness in two strains of mice. In the case of M. corti-infected ICR mice, a strong tumor growth suppression occurred, which was accompanied by a significant reduction in the formation of distant metastases in the liver and lung. Tapeworm-infected C57BL/6J mice also showed a suppression of tumor growth and, in addition, the overall survival of infected C57BL/6J mice was significantly improved. Experiments with potential cross-reaction of melanoma and tapeworm antigens with respective specific antibodies, restimulation of spleen T cells, or the direct effect of tapeworm excretory-secretory products on melanoma cells in vitro could not explain the phenomenon. However, infections with T. crassiceps and M. corti increased the number of leukocytes possibly involved in anti-tumor immunity in the peritoneal cavity of both ICR and C57BL/6J mice. This study unveils the complex interplay between tapeworm infections, immune responses, and melanoma progression, emphasizing the need for further exploration of the mechanisms driving observed tumor-suppressive effects.